2022
DOI: 10.3390/children9081137
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Gastroesophageal Reflux in Neonates with and without Preventive Anti-reflux Surgery at the Time of Congenital Diaphragmatic Hernia Repair

Abstract: One potential comorbidity after congenital diaphragmatic hernia (CDH) is gastroesophageal reflux (GER), which can have a substantial effect on patients’ quality of life, thriving, and complications later in life. Efforts have been made to reduce gastroesophageal reflux with a preventive anti-reflux procedure at the time of CDH repair. In this follow-up study of neonates participating in a primary RCT study on preventive anti-reflux surgery, symptoms of GER were assessed longitudinally. Long-term data with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…84 Even more challenging is determining the role of fundoplication to improve growth, prevent respiratory infections and manage esophagitis. 78 79 85 86 Prospective evaluation of concomitant fundoplication at time of CDH repair did not show a significant reduction in GERD symptoms in patients who underwent fundoplication compared with controls. Similarly, no difference in growth parameters was achieved at 2 years of age when comparing neonates who underwent fundoplication to controls.…”
Section: Pulmonary Protectionmentioning
confidence: 98%
See 1 more Smart Citation
“…84 Even more challenging is determining the role of fundoplication to improve growth, prevent respiratory infections and manage esophagitis. 78 79 85 86 Prospective evaluation of concomitant fundoplication at time of CDH repair did not show a significant reduction in GERD symptoms in patients who underwent fundoplication compared with controls. Similarly, no difference in growth parameters was achieved at 2 years of age when comparing neonates who underwent fundoplication to controls.…”
Section: Pulmonary Protectionmentioning
confidence: 98%
“…85 One of the largest studies from the French CDH Registry of over 700 neonates identified intrathoracic liver position, larger CDH defect size, prenatal diagnosis, and patch repair as predictive variables for fundoplication. 78 As an alternative to fundoplication to manage GERD, postpyloric tube feeding has been used in some centers.…”
Section: Pulmonary Protectionmentioning
confidence: 99%
“…Treating congenital diaphragmatic hernia (CDH), a rare and potentially life-threatening malformation of a newborn's diaphragm and lungs, does not end with surgical repair and patient discharge. Long-term morbidity in these patients is a well-known problem, especially in those with large defects [1,2]. As survival rates of patients with large defects increase, so does the need for a thorough follow-up accompanying these patients into transition and adulthood [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%